afla pe b: (b:4+19)×2-25=23
REPEDEEE
Răspunsuri la întrebare
Răspuns de
1
( b : 4 + 19 ) × 2 - 25 = 23
( b : 4 + 19 ) × 2 = 23 + 25
( b : 4 + 19 ) × 2 = 48
b : 4 + 19 = 48 : 2
b : 4 + 19 = 24
b : 4 = 24 - 19
b: 4 = 5
b = 5 × 4
b = 20
( b : 4 + 19 ) × 2 = 23 + 25
( b : 4 + 19 ) × 2 = 48
b : 4 + 19 = 48 : 2
b : 4 + 19 = 24
b : 4 = 24 - 19
b: 4 = 5
b = 5 × 4
b = 20
marcela16:
Cu plăcere!
Răspuns de
0
(b : 4 + 19) · 2 - 25 = 23 ⇔
⇔ (b : 4 + 19) · 2 = 25 + 23 = 48 ⇔
⇔ b : 4 + 19 = 48 : 2 = 24 ⇔
⇔ b : 4 = 24 - 19 = 5 ⇒ b = 4 · 5 = 20.
/rfd
Alte întrebări interesante
Matematică,
8 ani în urmă
Limba română,
8 ani în urmă
Matematică,
8 ani în urmă
Franceza,
9 ani în urmă
Limba română,
9 ani în urmă